2016
DOI: 10.1007/s10899-016-9612-z
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Harm and Crime Careers

Abstract: Incarcerated populations across the world have been found to be consistently and significantly more vulnerable to problem gambling than general populations in the same countries. In an effort to gain a more specific understanding of this vulnerability the present study applied latent class analysis and criminal career theory to gambling data collected from a sample of English and Scottish, male and female prisoners (N = 1057). Theoretical links between gambling and crime were tested through three hypotheses: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 31 publications
(34 reference statements)
3
47
1
Order By: Relevance
“…Blaszczynski and McConaghy (1994a) and Pastwa-Wojciechowska (2011) assertion that antisocial personality disorder is independent of gambling-related offending is striking as other studies have suggested that antisocial personality and its associated impulsive behaviours may be an underlying contributor to the commission of these crimes (e.g., May-Chahal, Humphreys, Clifton, Francis, & Reith, 2017; Meyer & Stadler, 1999). May-Chahal et al (2017) found a longitudinal link between loss-chasing and high rates of criminal behaviour that is perhaps indicative of underlying difficulties with impulse control. Similarly, Meyer and Stadler (1999) proposed that addictive gambling behaviour and impulsive antisocial personality factors directly influence criminal activity.…”
Section: Potential Causes Of Gambling-related Crimementioning
confidence: 98%
See 3 more Smart Citations
“…Blaszczynski and McConaghy (1994a) and Pastwa-Wojciechowska (2011) assertion that antisocial personality disorder is independent of gambling-related offending is striking as other studies have suggested that antisocial personality and its associated impulsive behaviours may be an underlying contributor to the commission of these crimes (e.g., May-Chahal, Humphreys, Clifton, Francis, & Reith, 2017; Meyer & Stadler, 1999). May-Chahal et al (2017) found a longitudinal link between loss-chasing and high rates of criminal behaviour that is perhaps indicative of underlying difficulties with impulse control. Similarly, Meyer and Stadler (1999) proposed that addictive gambling behaviour and impulsive antisocial personality factors directly influence criminal activity.…”
Section: Potential Causes Of Gambling-related Crimementioning
confidence: 98%
“…Where the focus of interviewing remains on offences motivated by obtaining money, participants might either fail to, or avoid, disclosing violent crimes for similar reasons. Therefore, reviewed studies relying on self-report may disguise a higher occurrence of violent gambling-related offences than the results indicate (Abbott, McKenna, & Giles, 2005;Tessenyi & Kovacs, 2016;Lloyd, Chadwick, & Serin, 2014;Templer, Kaiser, & Siscoe, 1993;May-Chahal, Humphreys, Clifton, Francis, & Reith, 2017;Preston et al, 2012;Pastwa-Wojciechowska, 2011;Turner, Preston, McAvoy, Saunders, & Jain, 2009;Blaszczynski & McConaghy, 1994a, 1994bGranero et al, , 2015Meyer & Stadler, 1999;Martin, MacDonald, & Ishiguro, 2012;Rudd & Thomas, 2016;Ledgerwood, Weinstock, Morasco, & Petry, 2007).…”
Section: General Limitations Of the Gambling-related Crime Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…12 months prior to imprisonment(May-Chahal et al 2012; Turner et al, 2012;May-Chahal et al 2017). Comparatively low rates of problem gambling were recorded across UK studies,with May-Chahal et al (2012) reporting that 10.4% of males and 5.9% of females surveyed were defined as problem gamblers, and May-Chahal et al (2017) identifying that 12.1% of a sample of 1057 male and female prisoners met the criteria for problem gambling.…”
mentioning
confidence: 99%